Single Feed Aperture-Coupled Wideband Dielectric Resonator Antenna with Circular Polarization for Ku-Band Applications - Joshua M. Patin; Satish K. Sharma (International Journal of Antennas and Propagation)
A novel single feed aperture-coupled wideband dielectric resonator antenna (DRA) exhibiting righ-handed circular polarization (RHCP) operating in the Ku-band frequency range is presented. The aperture-coupled single feed design utilizes back-side microstrip excitation through a novel bow-tie-shaped cross-slots in the ground plane. Extensive simulation parametric studies resulted in a 3 dB axial ratio (AR) bandwidth of 17.24% at a center frequency of 13 GHz, where the dielectric resonator is excited in its HEM11δ resonant mode. A prototype DRA was fabricated with some limitations and experimentally verified for the impedance matching and radiation patterns showing circular polarization.